Niemcy w procesie integracji europejskiej na tle kryzysu greckiego - MICHALAK, JAKUB (Rocznik Integracji Europejskiej, 2012)
Gerhard Schröder’s appointment as Chancellor of Germany in 1998 marked the first clear signs of Germany’s emancipation from the EU’s decision-making center in Brussels. It was, however, only after 2008, when the global economic crisis resonated across Europe, that Berlin maturely redefined its European policy priorities. Following that, the federal government gained more confidence in applying international policy tools to protect the German raison d’état in the Old Continent. For this reason Chancellor Angela Merkel has made the struggle with the financial problems of the eurozone one of the priorities of her second-term in office. The quality of bilateral cooperation between the leaders of Germany and France plays an important role in this respect, especially in view of Nicolas Sarkozy’s defeat in the latest presidential election. François Hollande has already proved that Paris has a different attitudeto the issue of the redistribution of the eurozone members’ debt than Germany, and reaching a consensus will require the CDU leader to be more submissive than before. Angela Merkel is aware of the ongoing reconfiguration of European political alliances, therefore she is prepared to soften Germany’s diplomatic language to maintain the stability of the European currency, to which Germany owes its current position in Community decision-making structures. The main focus of this paper is to explore the formula of „European solidarity” of Germany in the context of the eurozone debt crisis, with particular emphasis on the case of the Hellenic Republic. Angela Merkel’s standpoint is tested in the context of German-French cooperation with respect to the eurozone debt clearing policy.